Development of Smart Village Tourism in Kemuning through Digital Marketing and Product Diversification - Yuninata, Dama; Rohmawan Adi Pratama; Novi Ria Rahmawati; Wahyu Agung P; Eva Yuniarti Utami (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The development of Smart Village Tourism in Kemuning focuses on improving digital marketing strategies and diversifying tea products to improve the welfare of local communities and attract more tourists. Sumilir Valley, located in Kemuning Village, Ngargoyoso District, Karanganyar Regency, has considerable ecotourism potential because of its beautiful natural scenery and traditional tea plantations. Despite these assets, the village faces challenges such as limited market reach, inadequate infrastructure, and low digital literacy among the population, which hinders tourism and economic growth. This article describes the background, methods, results, and future plans for the project implemented in Lembah Sumilir, Kemuning Village. Utilizing a mixed-methods approach, data were collected through surveys, focus group discussions (FGDs). Through a series of targeted training modules, we aim to equip local communities with the skills necessary to effectively manage and promote their tea products, thereby driving economic growth and cultural preservation. Future plans include expanding this initiative to other regions and exploring additional growth opportunities in complementary sectors to ensure long-term sustainability and ongoing benefits to society.